Impaired in-vitro proliferation of hemopoietic precursors in HIV-1-infected subjects - Lunardi-Iskandar, Y.; Georgoulias, V.; Bertoli, A.M.; Augery-Bourget, Y.; Ammar, A.; Vittecoq, D.; Rosenbaum, W.; Meyer, P.; Jasmin, C. (Leukemia research, 1989)
Patients with acquired immunodeficiency syndrome (AIDS) and persistent lymphadenopathy syndrome (LAS) display significant hematological abnormalities of one or more cell lineages. In order to understand the pathophysiologic mechanisms leading to these abnormalities we studied the proliferation capacity of pluripotent and committed hemopoietic precursors using in-vitro colony assays. Anemia, leukopenia and thrombopenia were relatively frequent findings in HIV-infected subjects irrespectively of the patients' clinical status. The colony growth capacity of AIDS patients' GM-CFU and BFU-E was significantly decreased whereas no GEMM-CFU colonies could be obtained. There was no correlation between the number of BFU-E and GM-CFU colony number and the hemoglobin or the absolute number of polynuclear cells, respectively. The plating efficiency of both committed and pluripotent hematopoietic precursors from HIV infected patients could not be enhanced when additional exogenous recombinant GM-CSF, human interleukin 3 or erythropoietin were added in contrast to normal patients' cells. In addition, the impaired colony growth of these precursors could not be restored after adherent or T-cell depletion or the addition of normal allogenic irradiated adherent or/and T cells. Since this colony growth abnormality was also detected in HIV seropositive asymptomatic subjects our findings strongly suggest that the in-vitro growth of hematopoietic precursors is affected early after HIV-1 infection.